Large chromosomal deletions and heritable small genetic changes induced by CRISPR/Cas9 in rice - Zhou, Huanbin (Oxford University Press, 2014)
The Cas9/sgRNA of the CRISPR/Cas system has emerged as a robust technology for targeted gene editing in various organisms, including plants, where Cas9/sgRNA-mediated small deletions/insertions at single cleavage sites have been reported in transient and stable transformations, although genetic transmission of edits has been reported only in Arabidopsis and rice. Large chromosomal excision between two remote nuclease-targeted loci has been reported only in a few non-plant species. Here we report in rice Cas9/sgRNA-induced large chromosomal segment deletions, the inheritance of genome edits in multiple generations and construction of a set of facile vectors for high-efficiency, multiplex gene targeting. Four sugar efflux transporter genes were modified in rice at high efficiency; the most efficient system yielding 87–100% editing in T0 transgenic plants, all with di-allelic edits. Furthermore, genetic crosses segregating Cas9/sgRNA transgenes away from edited genes yielded several genome-edited but transgene-free rice plants. We also demonstrated proof-of-efficiency of Cas9/sgRNAs in producing large chromosomal deletions (115–245 kb) involving three different clusters of genes in rice protoplasts and verification of deletions of two clusters in regenerated T0 generation plants. Together, these data demonstrate the power of our Cas9/sgRNA platform for targeted gene/genome editing in rice and other crops, enabling both basic research and agricultural applications.